Rancang Bangun Sistem Stabilisasi Nyala Api Pada Kompor Portabel Menggunakan Sensor Ultrasonik Dan Sensor Suhu Dengan Metode Fuzzy - Aras Nizamul Aryo Anwar; Rizal Maulana; Wijaya Kurniawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Based on the official website of the Ministry of Energy and Mineral Resources, in the future to develop geothermal optimally, Indonesia needs an investment of more than US $ 15 billion. In 2014, the production of petroleum and fossil about 789 thousand bpn which decreased to 98% compared to the previous year there was a decrease of about 4.41% The decline in production is more due to the age of Indonesia's old oil field and natural disturbance (Ministry of ESDM RI). Saving energy is one of the smartest ways in life. From these problems the authors create a solution for saving the source of oil and fossil by way of designing flame stabilization tool on portable stove using ultrasonic sensor and temperature sensor with fuzzy method. The tool will work when getting data from ultrasonic sensors and DS18B20 temperature sensors with outputs getting a rotation servo that aims to open the gas valve on the stove to produce flame stabilization by using arduino uno microcontroller which will be displayed via 16x4 LCD. The test result states that the accuracy of the sensor to know the condition of the distance between the size of the diameter of the pan in accordance with the diameter of the pan and the sensor is a small pot (97%) medium pan (98%) large pan (95%). In testing the temperature sensor DS18B20 know the accuracy level with different diameter size that is small pot (98,2%) medium pot (98,4%) big pot (99,1%) this show in reading condition of water temperature inside big of small pot diameter DS18B20 sensors will accurately or not compare with thermometer to get error from every water temperature inside diameter of pot error that is small pot (1,84%) medium pot (1,6%) big pot (0,9%)